(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Biochar has been regarding as a potential soil amendment for sustainable soil health, crop growth and mitigating climate change. Thus, the present study was performed to assess the effects of different rates of two biochar amendments and inorganic NPK fertilizer on the growth and biomass yield of wheat under pot condition at Chittagong University, Bangladesh. The two biochars prepared from mustard oil cake and rice straw by slow pyrolysis technique at 350-450 ºC were applied separately to the pot soil at the rate of 0, 1, 2, 3, 4 and 5% (w/w) and inorganic NPK fertilizer were also separately applied to the soil at the rate of 0, ¼, ½, ¾ and 1 of the recommended rate. The amended pot soil was incubated for 2 weeks before sowing of wheat seeds and observed the initial changes of soil properties. After 2 weeks of equilibration, soil organic carbon (OC) and Olsen P were relatively higher increased with oil cake biochar (OCB) whereas soil pH, electrical conductivity (EC) and available K were shown relatively higher value with rice straw biochar (RSB). The growth parameters at different growth periods and biomass yield after harvest were recorded. The growth parameters such as plant height, leaf number, spike growth, root length, total fresh and dry biomass were increased significantly (p < 0.05) with different rates of biochar and fertilizer amendments. In biochar amendment, the highest total fresh biomass (50.77 g.pot-1), total dry biomass (32.27 g.pot-1) and above ground dry biomass (27.14 g.pot-1) were found with 5% OCB rate which were statistically identical with 1 NPK rate (p < 0.05). Overall, the growth performance and biomass yield with OCB amendment was relatively better than RSB amendment. Our results suggest that both biochar (OCB or RSB) could be used to improve soils properties and hence productivity. Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 56-71, 2024